Gamification as a catalyst: A longitudinal analysis of cyberbullying knowledge, motivational regulation, and active participation in Malaysian primary schools - Zulkafli, Syamsol Azhar; Saibon, Ramdzan Ali; Saibon, Jamalsafri (Journal of Islamic, Social, Economics and Development, 2025)
Purpose: Malaysia records some of the highest rates of cyberbullying victimization and perpetration among youth in Asia. Traditional didactic interventions often fail to engage "digital native" primary school students or foster long-term behavioral change. This study evaluates the efficacy of a culturally responsive gamified intervention, "Cyber-Wira," compared to traditional instruction in enhancing cyberbullying knowledge, shifting motivational regulation, and promoting active bystander participation. Methodology: The study employs a quasi-experimental longitudinal design with a pre-test, post-test, and delayed post-test (4-week follow-up). A total of 300 students (ages 10-12) from selected Malaysian primary schools will be assigned to either an experimental group (gamified module) or a control group (didactic lecture). The intervention is grounded in Self-Determination Theory (SDT), utilizing game mechanics to satisfy needs for autonomy, competence, and relatedness. Data will be analyzed using Mixed-Design Repeated Measures ANOVA and mediation analysis to examine the role of active participation. Findings: It is hypothesized that while both groups will show immediate knowledge gains, the gamified group will demonstrate significantly higher knowledge retention at the delayed post-test. Furthermore, the gamified group is expected to exhibit a motivational shift from external regulation (fear of punishment) to autonomous motivation (internal value) to defend victims, mediated by higher levels of active participation during the learning process. Significance: This research contributes to the Malaysia Education Blueprint 2013-2025 by validating a scalable, evidence-based digital intervention tool. It offers empirical insight into the psychological mechanisms, specifically motivation and participation, that drive effective cyber-safety education in a collectivist cultural context.